Pengaruh Menonton Film Drama Komedi Korea terhadap Emosi Positif pada Mahasiswa yang Sedang Menempuh Skripsi - Zuchrufia, Afnia Rosa (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstractÂ The goal of this research is to find out the influence of watching korean drama komedy movie toward university student which is take on thesis. This research was conducted using Pre-test and Post-test Control Group Design. Outcome of the positive emotion will be analysed by parametric statistics Independent-Samples T-Test method and assisted by SPSS 17.0 for windows. Different test results from the gained score between the experimental group and the control group obtained value t = 12.370, p = 0.000 (p <0.01), it means that there are differences in positive emotion score was very significant between the experimental group and the control group.Â Key word: positive emotion, Korean drama comedy movie, university student take on thesis.